Anthropocratic Republic? Theocracy, secularity and Kemalism in Turkey. (September 2019) - Houston, Christopher
Over the past three decades, many once taken for granted assumptions about processes of secularism have been questioned and revised. One unifying feature of these reassessments is recognition of the plurality of social–historical contexts of secularism[s], their contrasting political arrangements, and thus of individuals' radically different regional experiences of them. Given, then, both this variety of 'secular' political systems and the incomparability of subjects' perceptions about/of them, the question becomes whether we should grant the same word – secularism – to all of them? In this paper, I propose that we should not, and suggest the term anthropocracy to describe a particular modern project of political order. To illustrate the argument, I present an example of what I interpret to be an exemplary anthropocratic political system, that of the Turkish Republic. I conclude by illustrating certain advantages that accrue to our understanding of contemporary politics in Turkey and elsewhere by diagnosing its governing policies as anthropocratic.